A useful method for the practice of pneumatic retinopexy: Slit-lamp laser photocoagulation through the gas bubble - SEVİK, MEHMET ORKUN; KUBAT, BETÜL; DERİCİOĞLU, VOLKAN; ŞAHİN, ÖZLEM (My University, 2023)
This study aimed to demonstrate the laser retinopexy method through the gas bubble under a slit-lamp biomicroscope using a wide-field contact lens to treat rhegmatogenous retinal detachment (RRD) with pneumatic retinopexy (PR) and report its anatomical and functional results. This single-center, retrospective case series included RRD patients treated with PR using sulfur hexafluoride (SF6). The demographics, preoperative factors, and anatomical and functional outcomes were collected from the patient files. The single-procedure success rate of PR at postoperative 6th months was 70.8% (17/24 eyes), and the final success rate after secondary surgeries was 100%. The BCVA was better in the successful PR eyes at postoperative 3rd (p = 0.011) and 6th month (p = 0.016) than in failed eyes. No single preoperative factor was associated with PR success. The single-procedure success rate of PR using the laser retinopexy method through the gas bubble with a wide-field contact lens system seems comparable to the PR literature.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Tıp (çeşitli); Medicine (miscellaneous); laser retinopexy; pneumatic retinopexy; retinal detachment; sulfur hexafluoride; wide-field contact lens